Casos y cosas: semanario popular (Vol. 1, No. 22) - Imprenta La Region (My University, 1919)
SPANISH: Incluye: ¡Obreros!, Revelaciones...., Charlas femeninas.

ENGLISH: Includes: Workers!, Revelations ...., Women's Talks
Cases and things: popular weekly (Vol. 1, No. 22)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas